Meningkatkan Manajemen Usaha Pengusaha Kue Kering dengan Mengoptimalkan Potensi Lokal di Kecamatan Kapas Kabupaten Bojonegoro - Dewie Tri Wijayati Wardoyo; Harlina Meidiaswati; Trias Madanika Kusumaningrum; Nunik Dwi Kusumawati; Muhammad Rizky Ramadhan (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
ABSTRACTCommunity service is the contribution of higher education institutions to optimize community potential through various empowerment programs, for example strengthening micro, small and medium enterprises (MSMEs). Snacks and pastries are a potential business in several villages in the Kapas District, Bojonegoro Regency. Entrepreneurs who produce cakes and snacks are constrained by increasingly fierce competition, encourage business partners to lower the selling price of their products in order to compete. The increase in raw material prices further reduced the profit margins of entrepreneurs. Through training and mentoring, entrepreneurs are guided to calculate production costs, record simple financial reports and determine the appropriate selling price. Entrepreneurs are given the insight to be more creative in utilizing the potential of their surroundings as raw materials for their products, such as moringa leaves and banana stems as snacks. The training also provides knowledge on how to read market opportunities and increase product value through attractive packaging to increase sales value. The development of Bojonegoro tourism can be a marketing door, especially for products that are characteristic of Bojonegoro, such as ledre bananas and processed snake fruit as well as snacks from various commodities in the Kapas District. The results of the activities show that partners are satisfied with the activities carried out. The value of knowledge related to business management and marketing increased as seen from the posttest score. Furthermore, partners want assistance regarding the use of the latest digital platforms as promotional media. Keywords: Business Management, MSMEs, Cookies and Snack, Kapas District,  ABSTRAKPengabdian kepada masyarakat merupakan kontribusi perguruan tinggi untuk mengoptimalkan potensi masyarakat melalui berbagai program pemberdayaan misalnya penguatan wirausaha mikro dan kecil dan menengah (UMKM). Jajanan dan kue kering merupakan salah satu usaha potensial di beberapa desa di Kecamatan Kapas Kabupaten Bojonegoro. Pengusaha produsen kue dan makanan ringan terkendala persaingan yang makin ketat yang mendorong mitra pengusaha menurunkan harga jual produknya agar dapat bersaing. Kenaikan harga bahan baku makin menurunkan keuntungan pengusaha. Melalui pelatihan dan pendampingan, pengusaha dibimbing melakukan perhitungan biaya produksi, mencatat laporan keuangan secara sederhana dan menentukan harga jual yang sesuai. Pengusaha diberikan wawasan agar lebih kreatif memanfaatkan potensi sekitar sebagai bahan baku produknya, seperti daun kelor dan batang pisang sebagai makanan ringan. Pelatihan juga membekali pengetahuan bagaimana membaca peluang pasar dan meningkatkan nilai produknya melalui kemasan yang menarik untuk meningkatkan nilai jual. Perkembangan pariwisata Bojonegoro dapat menjadi pintu pemasaran khususnya produk-produk yang menjadi ciri khas Bojonegoro seperti pisang ledre dan olahan salak serta makanan ringan dari berbagai komoditas yang ada di Kecamatan Kapas. Hasil kegiatan menunjukkan mitra pengusaha puas dengan kegiatan yang dilaksanakan. Nilai pengetahuan terkait manajemen bisnis dan pemasaran meningkat dilihat dari nilai posttest. Selanjutnnya mitra pengusaha menginginkan pendampingan tentang pemanfaatan berbagai platform digital terbaru sebagai media promosi. Kata Kunci: Manajemen Usaha, UMKM, Kue Kering, Kecamatan Kapas,